The Influence of Seller Responsiveness, Price, and Payment Features Cash On Delivery -Check First on Purchase Decisions on the Shopee Application - Nizam, Muchamad Choirul; Asrori, Muhamad; Himmati, Risdiana (Westscience Press, 2025)
The transformation of people's shopping behavior is greatly influenced by the rapid development of digital technology and the COVID-19 pandemic situation. The shift in shopping patterns from traditional (offline) methods to bold methods is becoming increasingly apparent. Shopee is a popular bold shopping platform in Indonesia. This study aims to determine the effect of Seller Response, Price, and COD Payment Features–Check first on Purchase Decisions on Shopee. This study uses a quantitative method with an associative approach to analyze the relationship between variables. Sample selection was carried out purposively based on certain criteria. The data collection instrument was a questionnaire distributed via Google Form, and the data analysis process was carried out with the help of SPSS software. The results of the analysis show that the combination of Seller Responsiveness, Price, and COD Payment Features–Check first can influence purchase decisions on Shopee for students of UIN Sayyid Ali Rahmatullah Tulungagung. Individually, each of these variables also has a significant and good impact. The coefficient of determination test shows that the third factor has an influence of 53.8% on purchasing decisions.